2020
DOI: 10.1002/acr.24052
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Fatigue, Stress, and Depression: Role of Reduction in Stress Toward Improvement in Fatigue

Abstract: Objective Fatigue is common among individuals with systemic lupus erythematosus (SLE), but the causes are not well understood. Our objective was to examine perceived stress and depressive symptoms as predictors of fatigue in SLE. Methods Data from 2 years of the Lupus Outcomes Study (n = 650 patients), obtained through annual structured interviews, were used. Fatigue was measured with the Short Form 36 (SF‐36) vitality scale along with a variety of self‐report measures of disease, depression, and stress. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 44 publications
1
27
0
Order By: Relevance
“…Fatigue (expressed as reduced vitality in SF-36) and pain are the most common extraglandular symptoms reported by patients suffering from rheumatologic diseases [21][22][23]. In population-based studies, the prevalence of persistent fatigue reaches approximately 20% among healthy individuals and up to 70% in patients with autoimmune diseases [21,22]. The pathogenesis of persistent fatigue is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue (expressed as reduced vitality in SF-36) and pain are the most common extraglandular symptoms reported by patients suffering from rheumatologic diseases [21][22][23]. In population-based studies, the prevalence of persistent fatigue reaches approximately 20% among healthy individuals and up to 70% in patients with autoimmune diseases [21,22]. The pathogenesis of persistent fatigue is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Depression affects both physical and mental dimensions of fatigue in SLE. Additionally, depression is frequent in SLE patients (between 17 and 75% of patients), and some authors have mentioned that SLE contributes to depression through its neurological involvement, an autoimmune effect, and the emotional consequences of pain and disability [30][31][32]. Stress, which is a subjective negative perception of life events, which may be influenced by sociological and psychological factors and SLE burden, seems to mediate the relationship between depression and fatigue over time in SLE patients.…”
Section: Psychological Determinantsmentioning
confidence: 99%
“…Stress, which is a subjective negative perception of life events, which may be influenced by sociological and psychological factors and SLE burden, seems to mediate the relationship between depression and fatigue over time in SLE patients. Decline in stress has been associated with a meaningful improvement in fatigue in SLE [31]. Sleep disorders have also been shown to be common and significant predictors of fatigue, occurring in more than half of SLE patients [28,29,33,34].…”
Section: Psychological Determinantsmentioning
confidence: 99%
“…One study demonstrated that over a one-year period self-reported perceived stress mediated the relationship between fatigue and depression. 39 In another study of 515 patients, fatigue was reported by 90% sample population and associated with helplessness and abnormal illness-related behaviours over the course of approximately 4 years follow up. 9 In the univariable and multivariable analyses of baseline variables, using C3 with the best fatigue trajectory as the reference group, demonstrated that older age at diagnosis was associated with lower fatigue classes (C3 and C4).…”
Section: Discussionmentioning
confidence: 96%